Fuel Cell Modeling Strategic Roadmap: A Systematic Approach - Kompis, C.; Malek, K. (Fuel cells (Weinheim an der Bergstrasse, Germany), 2016)
Polymer electrolyte fuel cells (PEFCs) are promising electrochemical devices for the direct conversion of chemical energy of a fuel into useful electrical work with vast applications in automotive, stationary, and autonomous power. It is widely recognized that progress in PEFC technology is a multi‐disciplinary challenge and hinges on Research and Development (R&D) breakthroughs in design, fabrication, and implementation of innovative materials, processes, and system optimization. Fuel cell modeling, in particular, has been the subject of intense research in the past two decades, as it is of great importance to design and process optimizations. Building upon the insights obtained in a European Collaborative Research Program, we present an analysis of fuel cell modeling R&D roadmap by focusing on technical and market attributes and the inter‐relations therein. The roadmap is driven by three distinct outcomes – alpha, beta and commercial versions, reflecting the maturity of the multi‐scale software. All roadmap entries are organized in layers, namely Market and Business; Services; Products; High Level Targets; Technology; Science; and Enablers and Resources. This study contributes to a much needed foundation for further planning of potential R&D and demonstration projects of fuel cells for automotive and other emerging sectors.